The use of augmented reality technologies in tourism businesses from the perspective of UTAUT2 - Çalışkan, Gürkan; Yayla, İsa; Pamukçu, Hüseyin (Emerald, 2023)
PurposeAugmented reality is one of the technologies that developed and became widespread, especially after the 2000s. It is seen that innovations such as 3D virtual reality glasses, artificial intelligence-supported smart chatbots that communicate with customers in a virtual environment, keyless hotel systems, the Internet of Things, augmented reality applications, smart personal assistants, digital infrastructure concepts and face recognition systems are used in tourism businesses. The place and use of augmented reality technologies in tourism enterprises are discussed in this study. This study was evaluated from the perspective of UTAUT2. The purpose of this study is to examine the usability of augmented reality technologies in tourism businesses.Design/methodology/approachWithin the scope of the study, interviews were held with augmented reality application developers, digital marketing agencies and accommodation business managers. The obtained data were processed with the MAXQDA analysis program.FindingsIt has been determined that augmented reality is a useful and informative technological tool for tourists, it can help sales, promotion and marketing activities, and its usability potency in accommodation businesses is high.Originality/valueWhen the literature is reviewed, it is understood that the studies that apply to the opinions of the application developers and the managers of the accommodation establishments are limited. Therefore, this study has been prepared to contribute to the literature in this respect. This study examines and discusses the use of augmented reality technologies in tourism enterprises, the benefits and difficulties they will create from the perspective of application developers and accommodation business managers and their place in tourism enterprises. This study was evaluated from the perspective of UTAUT2. There is a need for research developed using UTAUT models in technology acceptance studies. In this respect, it will contribute to the literature.